MODERN METHODS OF DIAGNOSTICS OF HYPERANDROGENIA IN GYNECOLOGY - Ibragimova Nadia Sabirovna; Kuvandikov Golib Berdirasulovich (Scholar Express Journals, 2023)
Polycystic ovary syndrome is the leading cause of hyperandrogenism in gynecological practice. Hyperandrogenism, anovulation, and specific echographic features support this syndrome. For diagnosis, history data, specific clinical manifestations, ultrasound data, hormonal tests and laparoscopy are used
Keywords: Hyperandrogenism; polycystic ovary syndrome; medical history; clinical data